Between the Practical and the Problematic: ChatGPT in University Education for Business and Management Degrees - Serrano Malebrán, Jorge; Vidal-Silva, Cristian; Gómez-López, Romina; Campos-Núñez, Franco (Emerging Trends in Education, 2026)
This study analyzes the effect of ChatGPT use on the perceptions, concerns, and perceived ethics of university students enrolled in business-related programs in academic setting. Using a cross-sectional quantitative approach, a structured questionnaire was administered to 118 business students at a Chilean University. The theoretical model was assessed using partial least squares structural equation modeling (PLS-SEM). The results indicated that ChatGPT use significantly influenced perceptions of its usefulness as an academic tool, explaining 61.3% of the variance in this construct. In contrast, no significant relationship was observed with students’ concerns, suggesting functional yet unreflective appropriation of the tool. Furthermore, the perceived ethics construct was excluded from the final model due to limitations in convergent validity. These findings reveal a dissociation between the instrumental valuation of the tool and ethical problematization of its use. The study concludes by highlighting the need to integrate institutional policies and pedagogical strategies that promote the critical, ethical, and responsible use of generative artificial intelligence in university education in management and business.